Maximum allowable hp rating of 3-phase induction motor fed through a stand-alone constant V/f controlled DFIG via RSC - Sharawy, Mohamed; A. Shaltout, Adel; Mohammed Youssef, Omar El-Sayed; A. Al-Ahmar, Mahmoud; Abdel-Rahim, Naser; Sutikno, Tole (Bulletin of Electrical Engineering and Informatics, 2024)
This paper presents a scheme to start three-phase induction motors (IMs) directly connected to terminals of constant V/f controlled doubly fed induction generator (DFIG) through the rotor side converter (RSC). The proposed control is achieved by controlling the output voltage and frequency of stand-alone DFIG via controlling an injected voltage into the rotor circuit through the RSC. The control scheme provides a search for maximum rating of the three-phase IM which can be supplied from a DFIG. The search technique is based on using a simplified mathematical model to find the capability limits of the RSC and DFIG. It is found that these parameters depend on the stator frequency and rotor slip. Therefore, an investigation is performed to find the lowest frequency and the corresponding allowable maximum rating for the IM to be safely started. A typical example is provided in the paper for a 15 kW DFIG. It is shown that this generator could supply a three-phase IM with a maximum rating of 1-hp if it operated at nominal outputs, voltage and frequency, during start-up period. While, using the proposed technique, the same generator could start-up a three-phase IM with maximum power rating of 7.25 hp.